PELAKSANAAN PROGRAM ELEKTRONIK WARONG KUBE PKH DI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU TAHUN 2017 - Faisal Aula; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The target of government policy is to improve the lives of the people, who are oriented towards increasing the income of the community, especially those who have economic limitations. Based on the Republic of Indonesia's Minister of Social Affairs Regulation No. 25 of 2016 concerning Business Facility Development Assistance through Electronic Warong Gotong Royong Joint Business Group the Hope Family Program states that the establishment of PKH KUBE e-Warong aims to improve the welfare of beneficiary families. The problems in this research are: First, how is the implementation of PKH's Warong KUBE Electronic Program in Pekanbaru's Rumbai Pesisir District in 2017. Second, what are the factors that hinder the implementation of PKH's Warong KUBE Electronic Program in Pekanbaru's Rumbai Pesisir District in 2017. As for the purpose of this paper, namely: First, To find out the implementation of the PKH Electronic Warong KUBE program in Pekanbaru City Rumbai Pesisir District in 2017. Secondly, To find out the factors that hinder the implementation of PKH Warong KUBE Electronic program in Pekanbaru Rumbai Pesisir District in 2017. This research is qualitative research. This research was conducted in the District of Rumbai Pesisir. The techniques used to collect data in this study are (1) Observation, (2) Interview, and (3) Documentation. The conclusions of this study indicate that the electronic implementation of PKH Warong KUBE at the Pekanbaru City Social Service has not been optimal, which is evidenced by the lack of human resources in the escort section, and there is a lack of funds in the implementation team that descends on the field. Based on the results of the research that the researchers have done, the authors make suggestions that the Prosperous Indonesian Community Cooperatives (KMIS) can be formed so that the input of food in e-Warong can be easily controlled, regaining the poor in each region, the community is wiser in utilizing assistance given so that the benefits of the program can be felt in the long term. Key Words: Implementation, e-Warong KUBE PKH, Program